Ethical and legal aspects of AIDS in Portuguese Law. - de Faria, P L (1991)
HIV infection presents by its particular characteristics of contagion and by the fact that it is associated with human behaviours which are already object of social discrimination or criminal sanctions, new elements which shook the traditional legal means used in the fight against epidemics. In this context, the present article makes an analysis of the main ethical and legal problems posed by HIV infection, in the framework of Portuguese law, with special focus on: a) Conflict between the necessary protection of public health by the State and the protection of fundamental rights and freedoms of the citizens; b) Inadequacy of the existent laws to fight contagious diseases to HIV infection; c) Discrimination; d) Testing and compulsory hospitalization versus informed consent; e) Confidentiality; f) Voluntary contagion. One of the main conclusions of the article is that legislation, as a mean to fight HIV infection, must be essentially aimed to the increasing of educational and informational actions and not to the repression of situations which are, in rule, rare, as the voluntary or careless contagion.